HBA1C: A REVIEW OF NON-GLYCAEMIC VARIABLES - Retika, Novita (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: People at risk for diabetes and those with high HbA1c are monitored for sugar levels. Age, race, gender, erythrocyte turnover, anemia, pregnancy, Haemoglobin variations, thyroid, liver, HIV, and renal disorders impact HbA1c nonthermally. Different forms of hemoglobin have long been recognized to alter HbA1c production and measurement. This interference depends on the congenital disease that affects hemoglobin production and the HbA1c measurement method.The aim: This article showed non-glycaemic variables in HbA1c examination.Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done.Result: In the PubMed database, the results of our search brought up 102 articles, whereas the results of our search on SagePub brought up 87 articles. The results of the search conducted for the last year of 2013 yielded a total 34 articles for PubMed and 21 articles for SagePub. In the end, we compiled a total of 19 papers, 11 of which came from PubMed and eight of which came from SagePub. We included seven study that met the criteria.Conclusion: HbA1c is straightforward, accurate, and on-site. It can diagnose and predict diabetes in low- and middle-income countries and remote areas. Hyperglycemia—diabetes' biochemical hallmark—should be properly controlled to reduce complications. Age, ethnicity, gender, erythrocyte turnover, anemia, pregnancy, haemoglobin variations, thyroid, liver, HIV, and renal diseases affect HbA1c measurement.